ENHANCEMENT OF ANTIBIOTIC ACTIVITY OF COLICINE K AND ALTERATION OF SEROLOGICAL PROPERTIES OF COLICINE K AND ENDOTOXINS - van Vunakis, Helen (The Rockefeller University Press, 1965)
Hemoglobin, its chains, and myoglobin enhance the antibiotic activity of colicine K. These proteins also interact with colicine K and other O antigens to alter their serological activity. The hemoglobin proteins did not alter the serological activities of three Pneumococcus polysaccharides or T4 bacteriophage DNA antigens but did alter the antigenic activity of fetuin. Interaction of hemoglobin and colicine K resulted in a retardation of colicine K antibiotic moiety as measured by gel filtration but did not affect the gel filtration properties of the lipopolysaccharide moiety.